Mothers’ Lived Experiences in Preventing Toddler Diarrhea Using Local Wisdom Poda Na Lima: A Phenomenological Study - Elpiana Sari; Amvina Amvina; Fahrizal Alwi; Hotma Royani Siregar; Zainal Efendi Hasibuan (Indonesian Journal of Global Health Research, 2025)
Diarrhea remains one of the leading causes of morbidity and mortality among children under five in Indonesia. Prevention efforts based on local wisdom, such as Poda Na Lima, a traditional life philosophy of the Batak Angkola community, hold significant potential as a promotive and preventive approach to child health. This study aims to explore the experiences of mothers of children under five in implementing Poda Na Lima as a preventive measure against diarrhea in their children. A qualitative approach with a phenomenological method was employed. Participants were selected using purposive sampling, with the number determined by the principle of data saturation, resulting in a total of ten participants. Data were collected through in-depth interviews guided by a semi-structured interview protocol developed based on the five principles of Poda Na Lima. Thematic analysis was used to analyze the data. The findings of the study revealed five themes: maintaining cleanliness of the heart, maintaining personal hygiene, maintaining cleanliness of clothing, maintaining cleanliness of the home, and maintaining cleanliness of the yard. Mothers of young children perceive Poda Na Lima not merely as a traditional custom, but also as a guide for daily healthy living. Personal, family, and environmental hygiene practices are considered key to diarrhea prevention.